Intelligent Computing and Optimization Proceedings of the 6th International Conference on Intelligent Computing and Optimization 2023 (ICO2023), Volume 5 - Vasant, Pandian; Shamsul Arefin, Mohammad; Panchenko, Vladimir; Thomas, J. Joshua; Munapo, Elias; Weber, Gerhard-Wilhelm; Rodriguez-Aguilar, Roman (Lecture Notes in Networks and Systems, 2023)
XIX, 425 p. 142 illus., 102 illus. in color.